2019
DOI: 10.1101/871988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dengue virus non-structural protein 1 (NS1) use the scavenger receptor B1 as cell receptor in human hepatic and mosquito cells

Abstract: 15Dengue is the most common virus disease transmitted to humans by 16 mosquitoes. The dengue virus NS1 is a multifunctional protein that form part of 17 replication complexes. In addition, NS1 is also secreted, as a hexamer, to the 18 extracellular milieu. Circulating NS1 has been associated with dengue 19 pathogenesis by several different mechanisms. Cell binding and internalization 20 of soluble NS1 result in the disruption of tight junctions and in down regulation 21 of the innate immune response. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Besides, SR-BI is also acting as a receptor for entry of the Zika virus. 25 This observation could explain the alteration in lipid and lipoprotein metabolism in dengue patients.…”
Section: Role Of Sr-bi In Viral Infectionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides, SR-BI is also acting as a receptor for entry of the Zika virus. 25 This observation could explain the alteration in lipid and lipoprotein metabolism in dengue patients.…”
Section: Role Of Sr-bi In Viral Infectionsmentioning
confidence: 94%
“…This verdict proposed that ApoA1 drives flavivirus to interact with SR‐BI and subsequent entry. Besides, SR‐BI is also acting as a receptor for entry of the Zika virus 25 . This observation could explain the alteration in lipid and lipoprotein metabolism in dengue patients.…”
Section: Role Of Sr‐bi In Viral Infectionsmentioning
confidence: 97%
“…Studies have confirmed that mosGCTL-7 in mosquitoes is able to bind to the JEV envelope protein via an N-glycan at N154 in a calcium-dependent manner and promote viral infection through the mosGCTL-7/mosPTP-1 pathway (185). SRB1 in human hepatocytes and an SRB1-like receptor in mosquito cells acts as cell-binding proteins that bind to and facilitate internalization of DENV and Zika virus (ZIKV) NS1, resulting in high permeability of endothelial cells and downregulation of the innate immune response (186). In addition, knocking out GNBP in A. aegypti promotes clearance of DENV-2 (187).…”
Section: Immune Escapementioning
confidence: 99%